2013
DOI: 10.1161/atvbaha.112.300912
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 Promotes the Pro-Osteogenic Response of Human Aortic Valve Interstitial Cells via Modulation of ERK1/2 and Nuclear Factor-κB Activation

Abstract: Objective Calcific aortic valve disease is a leading cardiovascular disease in the elderly, and progressive calcification results in the failure of valvular function. Aortic valve interstitial cells (AVICs) from stenotic valves express higher levels of bone morphogenetic protein-2 (BMP-2) in response to Toll-like receptor 4 (TLR4) stimulation. We recently found that TLR4 interacts with Notch1 in human AVICs. This study tests the hypothesis that Notch1 promotes the pro-osteogenic response of human AVICs. Appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
81
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 31 publications
8
81
0
3
Order By: Relevance
“…Further, IL-37 Tg mice exhibit reduced aortic valve thickening and BMP-2 levels after prolonged exposure to LPS or feeding with a high fat diet. Mechanistic data show that IL-37 suppresses the activation of NF-κB and ERK1/2, two important pathways that regulate BMP-2 and ALP expression in human AVICs (12,13). It should be noted that diseased aortic valve tissue is heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, IL-37 Tg mice exhibit reduced aortic valve thickening and BMP-2 levels after prolonged exposure to LPS or feeding with a high fat diet. Mechanistic data show that IL-37 suppresses the activation of NF-κB and ERK1/2, two important pathways that regulate BMP-2 and ALP expression in human AVICs (12,13). It should be noted that diseased aortic valve tissue is heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, proinflammatory mediators, such as tumor necrosis factor-α, have been shown to up-regulate the expression of osteogenic factor bone morphogenetic protein-2 (BMP-2) and early osteoblastic differentiation biomarker alkaline phosphatase (ALP) in AVICs (6, 7). We and others have observed that stimulation of either Toll-like receptor (TLR) 2 or TLR4 induces the osteogenic responses characterized by the expression of BMP-2 and ALP, among several other osteogenic biomarkers, in human AVICs (8)(9)(10)(11)(12), leading to the formation of calcification deposits in vitro (11)(12)(13). Moreover, bacteria associated with chronic periodontal infection and bacterial agents have been detected in diseased human aortic valves (14,15), and inoculation of rabbits with oral bacteria induces aortic valve lesions (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, our previous studies demonstrated an important role of proinflammatory signaling pathways in mediating the osteogenic responses in human AVICs (13,20,29). Particularly, stimulation of TLR2 and TLR4 upregulates the expression of runt-related transcription factor, alkaline phosphatase and bone morphogenic protein-2 in human AVICs (29).…”
Section: Il-37 Inhibits Nf-jb Activation Mediated By Tlr2 and Tlr4mentioning
confidence: 91%
“…The MyD88-dependent pathway activates NF-κB and AP-1; the two transcription factors collectively regulate the expression of inflammatory mediators in most cell types (17). It has been demonstrated that the MyD88-mediated signaling pathway plays an important role in mediating tissue inflammation in many inflammation conditions, including myocardial ischemia-reperfusion injury (18), atherosclerosis (19) and cardiovascular calcification (20).…”
Section: Introductionmentioning
confidence: 99%